Composition Effect of Fe3O4 and Graphene Oxide on The Microstructure of Fe3O4-Graphene Oxide Nanocomposite - Damayani, Mifta (Department of Physics, Universitas Negeri Padang, 2024)
The manufacture of lithium ion batteries is a solution to future energy limitations, but lithium ion batteries have a high price. The best solution to overcome the high price of lithium ion batteries is to make lithium ion battery electrodes from Fe3O4 nanoparticles. To optimize the performance of Fe3O4, it will be combined with graphene oxide made from coconut shell. This study aims to analyze the effect of Fe3O4:Graphene Oxide composition (40%:60%, 30%:70%, and 20%:80% ratio) on the microstructure of Fe3O4-Graphene Oxide nanocomposite which includes crystal size, functional groups, and surface morphology. The method used to make graphene oxide is by using the modified hummers method because this method is faster, safer, and has higher efficiency. The mixture of Fe3O4 variation with graphene oxide will be characterized using XRD, FTIR, and SEM. The result of XRD obtained crystal size for Fe3O4-Graphene Oxide nanocomposite composition 40%: 60% is 44.73 nm, for the composition of Fe3O4-Graphene Oxide nanocomposite 30%: 70%, the crystal size is 39.71 nm, and for Fe3O4-Graphene Oxide 20% nanocomposite composition: 80%, the crystal size is 45.64 nm. FTIR results showed the presence of C-H, O-H, C≡C, C=O, C-O bonds, and the presence of Fe-O absorption peaks indicating the success of the Fe3O4 with graphene oxide composite. SEM analysis results showed that the surface morphology of Fe3O4-Graphene Oxide nanocomposite has a spherical structure, which can be seen that the more Fe3O4 composition in the composite, the larger the graphene oxide surface is covered.